PROBLEMATIKA ANAK SAH DALAM PERSPEKTIF HUKUM PERKAWINAN NASIONAL DAN PUTUSAN MK NOMOR 46 TAHUN 2010 - Aisyah Rasyid (Al-Risalah: Jurnal Hukum Keluarga Islam (Ahwal Al-Syakhsiyah), 2021)
AbstractThis research is a study of a legitimate child in relation to the national marriage law and the Constitutional Court Decision Number 46 of 2010. The root of the problem is "The position of the legitimate child in the legal system in Indonesia? "This issue is important to study because there is a difference of principle concerning the status of legitimate child of these two pieces of legislation. Children status authorized by Act 1 of 1974 Nomo marriage is child obtained through legitimate marriage, marriage made in accordance with his religion or belief and recorded under the provisions of the applicable laws. Children born of legitimate marriage are entitled to the rights of parents that nasab rights, living rights, inheritance and custody. While the Constitutional Court decision No. 46 of 2010. That the status of a legitimate child is a child born of a legitimate marriage and children born outside legal marriage but her biological father can be demonstrated through the recognition of the wife, the recognition of men concerned or proof through science and technology, such as DNA testing even if not registered they are entitled to the rights of both parents, or from the mother and the man who caused her birth or her biological father.